1987
DOI: 10.1302/0301-620x.69b3.3584186
|View full text |Cite
|
Sign up to set email alerts
|

The Chiari pelvic osteotomy. A long-term review of clinical and radiographic results

Abstract: We have reviewed a series of 94 Chiari pelvic osteotomies carried out from 1966 to 1982. In 83 hips the indication for surgery had been pain, and of these patients 73 (88%) had appreciable relief within one year of operation. The other 11 hips were all in children and were painless; in them the osteotomy had successfully stabilised progressive subluxation of the hip. At review after a mean follow-up of 10 years (range, 2 to 18 years) 68 previously painful hips were reassessed. Although function of the hips had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 0 publications
6
32
1
3
Order By: Relevance
“…Moreover the mean range of movements did not decrease in any directions following the surgery. Our results agree with other reports [23] which concluded that the range of movement at the hip had not been impaired by the Chiari procedure, although progressive osteoarthritis did eventually reduce this range. However, some authors [24] have reported significant loss of internal rotation after Chairi osteotomy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover the mean range of movements did not decrease in any directions following the surgery. Our results agree with other reports [23] which concluded that the range of movement at the hip had not been impaired by the Chiari procedure, although progressive osteoarthritis did eventually reduce this range. However, some authors [24] have reported significant loss of internal rotation after Chairi osteotomy.…”
Section: Discussionsupporting
confidence: 93%
“…Hogh et al [23] reported that gait is [7], although this is not a universal finding [25]. In our series 14 patients were relieved of the preoperative antalgic gait, but two patients developed a Trendelenberg gait.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…However, pain associated with subluxation or dislocation was reduced in 9 of the patients. Chiari osteotomy has been used to treat hip subluxation and dislocation resulting from neitromusculur disorders (Otte 1969, Chiari 1974, Purath 1979, Bohler 1983, Root 1987, Thompson et al 1987, Osterkamp et al 1988, Gamble et al 1990, Pope et al 1994, Dietz and Knutson 1995, Niethard et al 1995a, Root et al 1995, DDH (Chiari 1974, Salvati and Wilson 1974, De Waal Malefjt et al 1982, Moll 1982, Bohler 1983, Fernandez et al 1984, Bohler et al 1985, Hogh and MacNicol 1987, Matsuno et al 1992, Rigo et al 1994, Niethard et al 1995a, Legg-Perthes' diseuse (Chiari 1974, Lack et al 1987, Thompson et al 1987, Robinson et al 1988, Mike and Bellyei 1989 and posttraumutic dysplasia (Trousdale and Ganz 1994). Osteotomy potentially improves femoral head coverage.…”
Section: William R Osebold Edward L Lester and Patrice Watsonmentioning
confidence: 99%